AN ANALYSIS OF THE INTERPLAY BETWEEN THE TWIN PROVISIONS OF SECTION 48 OF THE NATIONAL ENVIRONMENTAL MANAGEMENT: PROTECTED AREAS ACT AND SECTION 48 OF THE MINERAL AND PETROLEUM RESOURCES DEVELOPMENT ACT, IN RESPECT OF “PROTECTED AREAS” - Clive Vinti (Obiter, 2017)
This note examines the interplay between the twin provisions of section 48 of the National Environmental Management: Protected Areas Act (57 of 2003) (NEMPA Act) and section 48 of the Mineral and Petroleum Resources Development Act (28 of 2002) (MPRDA), in respect of the concept of a “protected area”. In essence, section 48(1) of the NEMPA Act read with section 48(1) of the MPRDA, prohibit “prospecting” in “protected areas”. However, section 48(1)(b) of the NEMPA Act and section 48(2) of the MPRDA, permit “prospecting” in “protected environments” and in any land “reserved in terms of any other any law”, if written authorisation is acquired under specific strict conditions. “Prospecting” is defined as intentionally searching for any mineral through any method which disturbs the surface or subsurface of the earth, including any portion of the earth that is under the sea or under other water; or in or on any residue stockpile or residue deposit, in order to establish the existence of any mineral and to determine the extent and economic value thereof; or in the sea or other water on land (s 1 read with s 17 of the MPRDA). This issue of the relationship between section 48 of the NEMPA Act and section 48 of the MPRDA has yet to be appropriately adjudicated on by the courts and thus, this paper will assess the implications of their inevitable interaction and suggest an approach that the courts could take in the assessment of a prospecting licence granted in respect of a “protected area”.